2023
DOI: 10.1007/s12028-023-01857-4
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Monocyte-to-Lymphocyte Ratio and Hematoma Progression After Cerebral Contusion

Huajun Zhang,
Xiaochun Duan,
Yimiao Zhang
et al.

Abstract: Background The objective of this research was to examine the impact of the monocyte-to-lymphocyte ratio (MLR) on the advancement of hematoma after cerebral contusion. Methods The clinical information and laboratory test findings of people with cerebral contusion were retrospectively analyzed. Using the tertiles of MLR, the study participants were categorized into three groups, enabling the evaluation of the correlation between MLR and the advancement of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…There was no correlation between inflammation indexes and the Rh blood factor before or after birth in non-thrombophilia patients. MLR may serve as a potential indicator for predicting the progression of hematoma after cerebral contusion [59]. The MLR was significantly higher in the HELLP group than in the normal pregnant patient control group at the delivery time 12 [60].…”
Section: Discussionmentioning
confidence: 91%
“…There was no correlation between inflammation indexes and the Rh blood factor before or after birth in non-thrombophilia patients. MLR may serve as a potential indicator for predicting the progression of hematoma after cerebral contusion [59]. The MLR was significantly higher in the HELLP group than in the normal pregnant patient control group at the delivery time 12 [60].…”
Section: Discussionmentioning
confidence: 91%
“…There was no correlation between inflammation indexes and the Rh blood factor before or after birth in non-thrombophilia patients. MLR may serve as a potential indicator for predicting the progression of hematoma after cerebral contusion [43]. The MLR was significantly higher in the HELLP group than in the normal pregnant patient control group at the delivery time [44].…”
Section: Discussionmentioning
confidence: 94%
“…The neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and MLR are indicators of these immune cells. Numerous studies have demonstrated that these markers can predict the presence of systemic inflammation and may be helpful in the diagnosis of various disorders ( 8 , 20 , 21 , 31 ). Recently, some studies have shown that the high MLR is associated with the occurrence and progression of diabetes complications, including diabetic nephropathy, DR, and PAD ( 7 , 22 24 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely studied in various inflammation-related disorders, such as cancer, tuberculosis and cardiovascular diseases, and has proven to be a reliable biomarker of systemic inflammation ( 17 19 ). Elevated MLR has been associated with poor prognosis and accelerated disease progression in several disorders, including acute kidney injury and hematoma after cerebral contusion ( 20 , 21 ). Recently, some studies have shown that the MLR is associated with the occurrence and progression of diabetes complications, including diabetic nephropathy, diabetic retinopathy (DR), and PAD ( 7 , 22 24 ).It is reasonable to assume that MLR may play a significant role in the onset and progression of DFU, given the mounting body of research emphasizing its importance in diabetes complications ( 7 , 22 24 ).…”
Section: Introductionmentioning
confidence: 99%